Biochemical Analysis of Scatophagus argus (Spotted Scat)in the Kali River, Karwar - et al., Shireenbanu Maqbullahamed Chandrageri (International Journal of Advanced Science and Technology, 2019)
Animal proteins are considered to be comparatively economic source of food. Fish and Fish products plays a significant role in providing the nutrition rich food. Now a days, there exists a great demand for edible fish mainly due to their high specific nutritional content. Today’s generation have created awareness of healthy eatables and hence targets fish as a significant part of the diet. This research analyze the spotted scat (Scatophagus argus) that is widely distributed around the Sunkeri backwater, Kali River, Karwar.The biochemical composition of this sample have been under investigation for a period of 13 months from the month of April 2016 to April 2017.The fresh samples collected onboard is processed to record the moisture, lipid, protein, carbohydrate and ash content. The moisture content in male and female is recorded as 74% in male and 74.55%.The protein content of the specimen is recorded as 16.31% in male and 16.65 % in female. Corresponding lipid content is found to be 6.61% in male and 6.95 % in female fishes. Apart from that the carbohydrate percentage is found to be 0.66% in male and 0.76% in female. Finally the ash content of male and female fish is recorded as 6.61% and 6.95% respectively. These measures have been widely utilized in filling up the existing research gap around the study site.